Poor nutritional knowledge and food restrictions among families of children with cancer and their impact: A cross-sectional study of 700 families. Issue 5 (3rd September 2018) - Srivastava, Richa; Gupta, Vineet Govinda; Dhawan, Deepa; Geeta, Kumari; Bakhshi, Sameer
Abstract: Purpose: To determine the prevalence of poor food knowledge and food restrictions among families of children with cancer and assess their impact on nutritional outcomes. Methods: In this cross-sectional study of 700 families of children with cancer who attended a referral cancer clinic, parents were asked 9 questions about nutritional knowledge ("Knowledge score") and 12 questions about food restrictions ("Restriction score"). Secondary outcomes included the nutritional status of children and possible socio-demographic associations of poor food knowledge. Findings: Commercial foods were considered more nutritious than homemade foods. Restriction of protein and energy-rich foods was frequent. Low knowledge scores were associated with rural background, poverty, and illiteracy. Low parental knowledge scores were associated with low weight and low height of the child. High restriction scores were associated with low weight but not low height. Conclusions and implications: Harmful perceptions are widely prevalent in parents of children with cancer and targeted educational interventions may have a role in improving malnutrition in these children.